Early warning systems and rapid response to the deteriorating patient in hospital: A systematic realist review. (20th September 2017) - McGaughey, Jennifer; O'Halloran, Peter; Porter, Sam; Blackwood, Bronagh
Abstract: Aim: To determine the Rapid Response System programme theory and investigate how the mechanisms of implementation and the characteristics of context combine to enable or constrain the implementation of Rapid Response Systems and the achievement of desired outcomes. Background: Rapid Response Systems have been implemented internationally to improve the recognition and management of patient deterioration, reduce the need for cardiopulmonary resuscitation and improve patient outcomes. Design: Realist review. Data sources: We searched DARE, CENTRAL, NHSEED, MEDLINE, Medline In Process, EMBASE, CINAHL, PubMed, Scopus, The Web of Science and PychInfo databases from 1997 ‐ 2017 in addition to purposively searching the grey literature looking for articles supporting, refuting or explaining Rapid Response System programme theories. Review methods: Included studies were critically appraised and graded using the Critical Appraisal Skills Programme tool. Data extraction and synthesis investigated the Rapid Response System theoretical propositions against the empirical evidence to refine Rapid Response System programme theories. Results: The review found that the Rapid Response System programme theory achieved desired outcomes when there were sufficient skills mix of experienced staff, EWS protocols were used flexibly alongside clinical judgement and staff had access to ongoing, multiprofessional, competency‐based education. However, ward cultures, hierarchical referral systems, workload and staffing resources had a negative impact on the implementation of the Rapid Response System. Conclusion: To improve the recognition and management of patient deterioration, policymakers need to address those cultural, educational and organizational factors that have an impact on the successful implementation of Rapid Response Systems in practice.